EVALUATION OF SHALE GAS POTENTIAL IN KAZAKHSTAN - Lidiya Parkhomchik; Bela Syrlybayeva (Проблемы постсоветского пространства)
The article considers the primary evaluation of the shale gas resource potential in Kazakhstan, as well as defines the most problematic issues for the large-scale shale gas production over the state. The authors pay special attention to the national strategy of the Kazakhstani government in the sphere of the unconventional energy sources production, defining the possible technological and environmental problems for the shale gas extraction. The article also notes that implementation of the fracking technologies in the country could cause both positive and negative effects on the economy of Kazakhstan. Therefore, further steps in this direction should be based on the meaningful and comprehensive geological data regarding the shale gas potential.